Nested and Spillover Effects of Institutional Environment on IFRS Convergence: A Multilevel Approach and an Agglomeration Economy Perspective - Cao, June (Emerald, 2023)
Purpose The objective of this study is to examine how the heterogeneity of the institutional environments within a single country influences International Financial Reporting Standards (IFRS) convergence and earnings quality based on a meso- and multi-level approach.